The interaction effects of knowledge transfer on knowledge assets and innovative performance relationship - Norhafizah Abu Hasan; Nor Asiah Omar; Muhammad Nizam Zainuddin; Dzulkifli Mukhtar (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of the present study is to empirically test the relationship among knowledge assets, such as explicit and tacit knowledge on SMEs’ innovative performance. Furthermore, the contingent effects of speed, reliability and accuracy of knowledge transfer are also tested on the relationship. In which the theoretical framework was used to explain the Nonaka’s theory of knowledge creation and knowledge-based view theory. This is because the present study is conducted to evaluate a direct relationship between knowledge assets on innovative performance. Thus, the contingent effect of knowledge transfer on the aforementioned relationship was tested. In order to achieve the study aims, the used of a quantitative study was employed via online questionnaires sent to SMEs. Multiple regression and interaction effect tests were utilised using SPSS25 software. The findings revealed three important outcomes. Firstly, knowledge assets have positive relationship with innovative performance. Secondly, speed of knowledge transfer positively influences knowledge assets and innovative performance relationship. Thirdly, reliability and accuracy of knowledge transfer also positively influence knowledge assets and innovative performance relationship. This result demonstrates that with the right management of knowledge, especially in making sure that knowledge is transferred to the right people, innovative performance especially in SMEs can be elevated.